Growth method for controlling molybdenum disulfide crystal layer number and stacking structure based on temperature gradient and application of growth method
Through the chemical vapor deposition method controlled by temperature gradient, using MoO3, sulfur powder and sodium chloride auxiliary agent, the precise control of the number of layers and stacking structure of MoS2 crystals is achieved, solving the problem of MoS2 crystal growth control in the existing technology, and improving the Its photoelectric properties.
Patent Information
- Application Number
- CN202411421041.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The prior art is difficult to achieve large-area uniformity, layer controllability and high crystal quality of molybdenum disulfide (MoS2) crystals simultaneously, especially the control difficulties in stacking structures, which affect their photoelectric performance.
Using a chemical vapor deposition method based on temperature gradient control, MoO3 powder and sulfur powder are used as precursors, and sodium chloride is added as auxiliary agents. By adjusting the growth temperature from 700-900℃, the accuracy of the number of layers and stacking structure of MoS2 crystals is achieved. Regulation.
It realizes high-quality growth from single-layer to four-layer MoS2 crystals, significantly improves the growth control and photoelectric response characteristics of the material, and provides a technical basis for high-performance photodetectors.
Smart Images

Figure CN119308017A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional layered materials and optoelectronic materials, and in particular relates to a growth method and application thereof for controlling the number of molybdenum disulfide crystal layers and stacking structure based on a temperature gradient. Background Art
[0002] In recent years, with the widespread application of two-dimensional transition metal dichalcogenides (TMDCs) in photodetection and electronic devices, the fine control technology of their layer number and stacking structure has attracted widespread attention. TMDCs are considered to be ideal materials for high-performance photodetectors due to their unique tunable band gap, excellent nonlinear optical properties and good material compatibility. However, although a variety of methods have been used to synthesize these materials, especially the preparation of high-quality single-layer and multi-layer molybdenum disulfide (MoS2) crystals through chemical vapor deposition (CVD) technology, there are still major challenges in precisely controlling the number of layers and stacking order.
[0003] Existing CVD methods generally have difficulty in achieving large-area uniformity, controllable number of layers, and high crystal quality at the same time. Many experiments have shown that the number of layers of TMDCs can be controlled within a certain range by adjusting the growth temperature, reaction atmosphere, and substrate material, but for structures with more than three layers, it is still very difficult to control the stacking order. These challenges mainly stem from the complexity of TMDCs in anisotropic growth and the difficulty in regulating thermodynamic and kinetic processes. During the CVD growth process, factors such as temperature and precursor concentration directly affect the nucleation and growth behavior of the material, making it difficult to simultaneously achieve large-size crystals, ultra-thin thickness, and controllable stacking structures. More importantly, different stacking structures will significantly affect the optoelectronic properties of TMDCs, so precise control of the number of layers and stacking structures is crucial for the design of next-generation high-performance devices.
[0004] Therefore, there is an urgent need to develop a synthesis method that can accurately control the number of TMDCs layers and the stacking order, which can effectively improve their performance in the fields of photoelectric detection and energy conversion. Summary of the invention
[0005] To solve the above technical problems, the present invention proposes a method for controlling the growth of the number of layers and stacking structure of molybdenum disulfide crystals based on temperature gradient and its application. The method of the present invention is highly controllable and repeatable, and provides an efficient technical means for the preparation of large-area, high-quality molybdenum disulfide materials, solving the technical problem of uncontrollable number of layers and stacking structure of multilayer materials. The method of the present invention is precisely controlled and is suitable for preparing high-performance optoelectronic materials with a specific number of layers and stacking structure.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A growth method for controlling the number of layers and stacking structure of molybdenum disulfide crystals based on temperature gradient, using molybdenum trioxide (MoO3) powder and sulfur (S) powder as precursors, sodium chloride (NaCl) as an auxiliary agent, and chemical vapor deposition. The growth temperature is controlled at 700-900°C to obtain MoS2 crystals with controllable number of layers and stacking structure.
[0009] Preferably, the mass ratio of the MoO3 powder, the sulfur powder and the sodium chloride is 1:100:0.1. For example, when the mass of the MoO3 powder is 1.0 mg, the mass of the S powder is 100 mg, and the mass of the NaCl is 0.1 mg.
[0010] Preferably, the chemical vapor deposition step includes: mixing the MoO3 powder and the NaCl and placing them at the heat source center of a tubular furnace, placing the S powder upstream of the tubular furnace 15 cm away from the heat source center, placing a Si / SiO2 substrate face to face with the MoO3 powder and the NaCl, and placing the Si / SiO2 substrate directly above the MoO3 powder and the NaCl, heating to the growth temperature for crystal growth, cooling to room temperature after the growth is completed, and obtaining MoS2 crystals with controllable number of layers and stacking structure.
[0011] Preferably, the distance between the MoO3 powder and the NaCl and the Si / SiO2 substrate is 4 mm.
[0012] Preferably, the Si / SiO2 substrate also includes a pretreatment step before use; the pretreatment method is: cutting the wafer-level Si / SiO2 into independent substrates of 1cm×1cm in size, ultrasonically cleaning them with ultrapure water, acetone, isopropanol and ethanol respectively, with an ultrasonic power of 40W, each ultrasonic cleaning for 10 minutes, and finally blowing dry with nitrogen to use as the crystal growth surface.
[0013] Preferably, a single-layer MoS2 crystal is obtained at a growth temperature of 700°C, a double-layer MoS2 crystal is obtained at a growth temperature of 720°C, a triple-layer MoS2 crystal is obtained at a growth temperature of 850°C, and a quadruple-layer MoS2 crystal is obtained at a growth temperature of 900°C.
[0014] Preferably, during the chemical vapor deposition, the crystal growth time is controlled to be 5 minutes.
[0015] The second technical solution of the present invention:
[0016] The present invention also provides a MoS2 crystal with controllable number of layers and stacking structure obtained by the above growth method.
[0017] Preferably, the MoS2 crystal has a single layer thickness of 0.71 nm, a double layer average thickness of 1.26 nm, a triple layer average thickness of 1.85 nm, a quadruple layer average thickness of 2.29 nm, and a maximum lateral dimension of 210 μm.
[0018] The third technical solution of the present invention:
[0019] The present invention also provides the application of the MoS2 crystal with controllable number of layers and stacking structure in the field of optoelectronics. For example, the MoS2 crystal of the present invention can be prepared into a photodetector with a photosensitivity of 2.3×10 3 , the response rate is 3.3×10 4 A.W. -1 , the detection rate can reach 1.7×10 14 Jones. The MoS2 crystal of the present invention can also be prepared into a polarization-sensitive photodetector.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects:
[0021] 1. The present invention adopts a temperature-driven strategy, which can accurately control the number of layers and stacking structure of MoS2 crystals, successfully realize multiple stacking methods from single layer to four layers, and significantly improve the growth controllability of the material. Through precise control of temperature, the present invention can obtain high-quality multilayer MoS2 crystals with excellent photoelectric response characteristics.
[0022] 2. The present invention adopts the dual coupling mechanism of temperature gradient and NaCl auxiliary agent to jointly realize the precise control of the number of layers of MoS2 crystals. The temperature gradient is mainly used, and the addition of an appropriate amount of NaCl is used as a supplement to determine the optimal growth conditions of MoS2 crystals, providing a basis for the preparation of high-quality, customized two-dimensional materials with multiple layers.
[0023] 3. The chemical vapor deposition (CVD) method provided by the present invention is efficient and convenient. During the growth process, no major changes to the existing CVD device are required. Only the growth temperature needs to be adjusted to achieve the synthesis of high-quality MoS2 crystals with controllable number of layers on a large-area substrate.
[0024] 4. The present invention has high controllability and can effectively solve the problem of unstable MoS2 multilayer stacking structure. By accurately adjusting the number of layers and the stacking sequence, the present invention provides a solid technical foundation for the application of two-dimensional material devices based on stacking engineering, especially the development of high-performance photodetectors. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0026] Figure 1 A schematic diagram of the positional relationship between the reaction precursor and the substrate in the growth method for controlling the number of MoS2 layers and the stacking structure based on the temperature gradient provided by the present invention;
[0027] Figure 2 A schematic diagram of the crystal growth process of the controllable growth method of the MoS2 layer number and stacking structure controlled by two-dimensional temperature gradient provided by the present invention;
[0028] Figure 3 A large-scale optical microscope image of a single-layer MoS2 prepared in Example 1 (a), an optical microscope image of a single crystal of a single-layer MoS2 (b), a Raman imaging image of a single-layer MoS2 (c), a large-scale scanning electron microscope image of a single-layer MoS2 (d), and a scanning electron microscope image of a single MoS2 crystal (e), and size statistics of the single-layer MoS2 crystals in a large-scale field of view (f);
[0029] Figure 4 Schematic diagrams of the atomic structures of two stacking configurations of the two-dimensional double-layer MoS2 prepared in Example 2 (AA and AB correspond to 3R phase and 2H phase, respectively), high-resolution transmission electron microscopy images of the two stacking configurations of the double-layer MoS2 (c, d), high-angle annular dark-field scanning transmission electron microscopy images of the two stacking configurations of the double-layer MoS2 (e, f), and selected area electron diffraction patterns of the two stacking configurations of the double-layer MoS2 (g, h);
[0030] Figure 5 Schematic diagram of four stacking configurations of the two-dimensional three-layer MoS2 prepared in Example 3 (a), optical microscope images of the four stacking configurations (b), second harmonic generation mapping images of the four stacking configurations (c), Raman spectra of the three-layer MoS2 with four different stacking configurations (d), displacement distances of two characteristic peaks in the Raman spectra of different stacking structures extracted from (d) (e), fluorescence spectra of the three-layer MoS2 with four different stacking configurations (f), displacement distances of two exciton peaks in the fluorescence spectra of different stacking structures extracted from (f) (g);
[0031] Figure 6 Schematic diagram and optical microscope image of eight stacking configurations of two-dimensional four-layer MoS2 prepared in Example 4 (a), Raman spectra of three-layer MoS2 with eight different stacking configurations (b), and fluorescence spectra of three-layer MoS2 with eight different stacking configurations (c);
[0032] Figure 7Stokes and Anti-Stokes ultra-low frequency Raman spectra of double-layer MoS2 in AA and AB stacking structures of Example 2, including spectra under unpolarized (un), parallel polarization ( / / ) and perpendicular polarization (⊥) conditions (a, b), the inset shows the vibration schematic diagram of shear mode (SM, purple area) and breathing mode (BM, green area) and the position of their characteristic peaks, the intensity ratio of BM and SM in double-layer MoS2 and the intensity ratio of parallel and perpendicular polarizations (c), Stokes and Anti-Stokes Raman spectra of three-layer MoS2 in four stacking structures of Example 3, including spectra under unpolarized (un), parallel polarization ( / / ) and perpendicular polarization (⊥) conditions (d), the intensity ratio of parallel polarization ( / / ) and perpendicular polarization (⊥) in a three-layer system (e), theoretical calculation of the electronic band structure of single-layer to four-layer MoS2 in Examples 1-4 (f);
[0033] Figure 8 The angle-resolved polarization Raman spectrum (a) of the parallel polarization configuration and the angle-resolved polarization Raman spectrum (b) of the perpendicular polarization configuration of the two-dimensional monolayer MoS2 prepared in Example 1, the angle-resolved polarization Raman spectrum (c) of the parallel polarization configuration and the angle-resolved polarization Raman spectrum (d) of the perpendicular polarization configuration of the AA(A) stacking configuration in Example 2-4, the angle-resolved polarization Raman spectrum (e) of the parallel polarization configuration and the angle-resolved polarization Raman spectrum (f) of the perpendicular polarization configuration of the AB(B) stacking configuration in Example 2-4;
[0034] Fig. 9 Optical microscope images of MoS2 crystals prepared by adding different amounts of NaCl in Comparative Examples 1 to 5, wherein "NaCl 1.0 mg" represents Comparative Example 2, "NaCl 0.8 mg" represents Comparative Example 3, "NaCl 0.5 mg" represents Comparative Example 4, "NaCl 0.3 mg" represents Comparative Example 5, and "Without NaCl" represents Comparative Example 1;
[0035] Fig.10 Optical microscope images of MoS2 crystals with different numbers of layers grown at different growth temperatures (700°C, 720°C, 850°C and 900°C) in Examples 1 to 4;
[0036] Fig.11 This is an optical microscope image of a MoS2 crystal grown at a growth temperature exceeding 900°C in Comparative Example 6;
[0037] Fig.12 IV curves (a) of the photodetector based on the single-layer MoS2 crystal prepared in Example 1 under light sources of different wavelengths, photosensitivity (b), responsivity (c) and detection rate (d) under different light intensities;
[0038] Fig.13 IV curves (a) of the photodetector based on the single-layer MoS2 crystal prepared in Example 1 at different light intensities at 405 nm, photosensitivity (b), responsivity (c) and detection rate (d) at different light intensities;
[0039] Fig.14 Schematic diagram of the structure of the polarization-sensitive photodetector prepared in Example 1 (a), IT curve of the polarization-dependent photocurrent response of 1-3 layers of MoS2 crystals prepared in Examples 1-3 (b), polarization-dependent photocurrent polar coordinate diagram (c) and characteristic light response time curve in fast scanning mode (d). DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] All raw materials used in the examples of the present invention are commercially available.
[0046] An embodiment of the present invention provides a growth method for controlling the number of layers and stacking structure of molybdenum disulfide crystals based on a temperature gradient. MoO3 powder and S powder are used as precursors, NaCl is used as an auxiliary agent, and chemical vapor deposition is performed to control the growth temperature to 700-900°C to obtain MoS2 crystals with controllable number of layers and stacking structure.
[0047] The temperature gradient of the present invention varies from 700 to 900°C. The present invention suppresses the random appearance of multiple layers by precisely controlling a series of temperature gradients, promotes the growth of MoS2 monolayer to four layers at a specific temperature, and each temperature corresponds to a specific number of layers, and rarely other numbers of layers appear, proving the effectiveness of temperature control of the number of layers, and these stacking structures with different numbers of layers have also been fully verified. In the present invention, the growth temperature affects the nucleation and growth rate of the crystal. Specifically, a higher temperature can provide more energy, promote the diffusion of the material on the substrate, increase the lateral growth rate of the material, and gradually stack multiple monolayers to form a multilayer structure. By controlling the growth temperature, controllable preparation of MoS2 with different numbers of layers is achieved. The present invention controls the growth temperature within the above range, which is conducive to obtaining MoS2 crystals with controllable number of layers and stacking structure; at the same time, at the above temperature, the precursor MoO3 and the auxiliary agent NaCl will both volatilize, and the precursor MoS2 will nucleate and grow epitaxially on the surface of the SiO2 / Si substrate. As an auxiliary agent, NaCl plays a key role: it generates non-volatile liquid alkali metal molybdate on the substrate, reduces the nucleation density of MoS2, inhibits the occurrence of multi-layer disordered stacking, and accelerates the lateral growth of MoS2. This method ensures that the number of MoS2 layers can be accurately controlled under different temperature conditions, from single layer to four layers, with very few other layers, verifying the effectiveness of temperature control on the number of layers, and the stacking structures with different numbers of layers have also been fully verified.
[0048] In the embodiments of the present invention, MoO3 is in powder form with a purity higher than 99.5%; NaCl is in powder form with a purity higher than 99.9%; S is in powder form with a purity not lower than 99.5%.
[0049] In an embodiment of the present invention, the MoO3 powder and the NaCl are mixed and placed at the heat source center of a tubular furnace, the S powder is placed upstream of the tubular furnace 15 cm away from the heat source center, the SiO2 surface of the Si / SiO2 substrate is placed face to face with the MoO3 powder and the NaCl, and the Si / SiO2 substrate is placed directly above the MoO3 powder and the NaCl, the temperature is raised to the growth temperature for crystal growth, and the temperature is lowered to room temperature after the growth is completed. The final crystal is grown on the SiO2 surface to obtain a MoS2 crystal with controllable number of layers and stacking structure.
[0050] In an embodiment of the present invention, the distance between the MoO3 powder and the NaCl and the Si / SiO2 substrate is 4 mm.
[0051] In an embodiment of the present invention, the Si / SiO2 substrate further includes a pre-treatment step before use; the pre-treatment method is: Si / SiO2 of wafer-level size is cut into independent substrates of 1cm×1cm size, and ultrasonically cleaned with ultrapure water, acetone, isopropanol and ethanol respectively, with an ultrasonic power of 40W, each ultrasonic cleaning for 10 minutes, and finally blown dry with nitrogen to serve as a crystal growth surface. The substrate has good thermal stability and can withstand temperature changes during high-temperature CVD, so that MoS2 with different layers can grow stably.
[0052] In an embodiment of the present invention, the Si / SiO2 substrate is in the form of a sheet, and the number is one sheet.
[0053] In an embodiment of the present invention, a single-layer MoS2 crystal is obtained at a growth temperature of 700°C, a double-layer MoS2 crystal is obtained at a growth temperature of 720°C, a triple-layer MoS2 crystal is obtained at a growth temperature of 850°C, and a quadruple-layer MoS2 crystal is obtained at a growth temperature of 900°C.
[0054] In an embodiment of the present invention, during the chemical vapor deposition, the crystal growth time is controlled to be 5 minutes.
[0055] In an embodiment of the present invention, the heating rate of heating to the growth temperature is 20° C. / min.
[0056] In an embodiment of the present invention, the cooling rate from the temperature down to the room temperature is 12° C. / min.
[0057] In the embodiment of the present invention, the vapor deposition uses Ar gas as a carrier gas for transporting gas; the flow rate of the Ar gas is 50-70 sccm.
[0058] In the embodiment of the present invention, the thinnest thickness of the MoS2 crystal with controllable two-dimensional layer number and stacking structure is 0.71nm for a single layer, 1.26nm for a double layer, 1.85nm for a triple layer, 2.29nm for a quadruple layer, and 210μm for a maximum lateral dimension. The MoS2 crystal with controllable two-dimensional layer number and stacking structure provided by the present invention has ultra-high quality and large lateral dimension.
[0059] The technical solution of the present invention is further illustrated by the following embodiments.
[0060] Example 1
[0061] S1. Cut wafer-level Si / SiO2 into independent substrates of 1 cm×1 cm in size. The Si / SiO2 substrates are ultrasonically cleaned with ultrapure water, acetone, isopropanol and ethanol, respectively, with an ultrasonic power of 40 W and each ultrasonic cleaning lasting 10 min. Finally, they are dried with a nitrogen gun for later use.
[0062] S2, using the SiO2 / Si with a size of 1 cm×1 cm obtained by the above process as a growth substrate;
[0063] S3, MoO3 powder with a purity higher than 99.95% and S powder not lower than 99.95% as precursors, and NaCl powder with a purity higher than 99.99% as an auxiliary agent;
[0064] S4, weigh 1.0 mg MoO3 powder and 0.1 mg NaCl powder, and weigh 100 mg S powder, and place them at the heat source center and upstream of the tube furnace respectively, and at the same time place the SiO2 / Si substrate in step S2 4 mm above the MoO3 powder and NaCl powder;
[0065] S5. Heat the tube furnace at a heating rate of 20°C / min from room temperature to 700°C, and use Ar gas as a carrier gas with a flow rate of 50 sccm. When the temperature reaches 700°C, use a magnet to move the ceramic boat containing S powder closer to the center of the heating source, and finally keep the distance from MoO3 powder and NaCl powder at 4 cm.
[0066] S6. Keep the temperature at 700°C for 5 min for crystal growth, and then cool the system temperature to room temperature at a cooling rate of 12°C / min in an Ar atmosphere to obtain a single-layer MoS2 sample.
[0067] Figure 1 Schematic diagram of the positional relationship of the precursor and auxiliary agent in the controllable growth method of the number of MoS2 layers and stacking structure controlled by the temperature gradient provided by the present invention, wherein the yellow is S powder, the purple is MoO3 powder, the blue is NaCl powder, and the pink is Si / SiO2 substrate. It can be seen that the MoO3 powder and the NaCl powder are located at the heat source center of the tube furnace, the S powder is located upstream of the tube furnace, and the Si / SiO2 substrate is located directly above the MoO3 and NaCl powders.
[0068] Figure 2 A schematic diagram of the crystal growth process of the controllable growth method of the MoS2 layer number and stacking structure provided by the present invention using a temperature gradient. It can be seen that the number of MoS2 layers can be controlled by controlling a series of temperature gradients from low to high. Specifically, a higher temperature can provide more energy, promote the diffusion of the material on the substrate, increase the lateral growth rate of the material, and allow multiple single layers to gradually stack to form a multilayer structure.
[0069] Figure 3 The large-scale optical microscope image of the single-layer MoS2 prepared in Example 1 (a), the optical microscope image of a single crystal of the single-layer MoS2 (b), the Raman imaging image of the single-layer MoS2 (c), the large-scale scanning electron microscope image of the single-layer MoS2 (d) and the scanning electron microscope image of a single MoS2 crystal (e), and the size statistics of the single-layer MoS2 crystals in the large-scale field of view (f). It can be seen that the single-layer distribution is indeed in a large area, and the Raman spectrum can also verify its single layer and characteristics and high quality. Figure 3 In (a) and (d), we can see that small triangles with uniform brightness grow over a large area of the substrate, which confirms that their thickness is comparable. In the magnified optical microscope and scanning electron microscope images, the thickness of the individual triangles is consistent and uniform. In addition, the triangular morphology proves that it is in the most stable morphology, proving that the MoS2 crystal with controllable number of layers and stacking structure has been successfully prepared.
[0070] Example 2
[0071] The difference from Example 1 is that in step S5, the temperature is raised to 720°C and maintained at 720°C for 5 minutes to perform double-layer crystal growth.
[0072] Figure 4 Schematic diagrams of the atomic structures of two stacking configurations of the two-dimensional double-layer MoS2 prepared in Example 2 (AA and AB correspond to 3R phase and 2H phase, respectively), high-resolution transmission electron microscopy images of the two stacking configurations of the double-layer MoS2 (c, d), high-angle annular dark field scanning transmission electron microscopy images of the two stacking configurations of the double-layer MoS2 (e, f), and selected area electron diffraction patterns of the two stacking configurations of the double-layer MoS2 (g, h); It can be seen that the two stacking configurations of the double-layer MoS2 are fully demonstrated under high-resolution and atomic-level characterization, which also verifies the high-quality single-crystalline properties of the double-layer MoS2.
[0073] Example 3
[0074] The difference from Example 1 is that in step S5, the temperature is raised to 850°C and maintained at 850°C for 5 minutes to perform three-layer crystal growth.
[0075] Figure 5Schematic diagram of four stacking configurations of two-dimensional three-layer MoS2 prepared in Example 3 (a), optical microscope images of the four stacking configurations (b), second harmonic generation mapping images of the four stacking configurations (c), Raman spectra of three-layer MoS2 with four different stacking configurations (d), displacement distances of two characteristic peaks in the Raman spectra of different stacking structures extracted from (d) (e), fluorescence spectra of three-layer MoS2 with four different stacking configurations (f), displacement distances of two exciton peaks in the fluorescence spectra of different stacking structures extracted from (f) (g); It can be seen that the four stacking configurations of three-layer MoS2 are fully demonstrated under the characterization of Raman spectrum, fluorescence spectrum and second harmonic generation, and the intrinsic differences of the four stacking configurations are also verified by the displacement difference of Raman characteristic peaks and the difference of two exciton peaks in fluorescence spectrum.
[0076] Example 4
[0077] The difference from Example 1 is that in step S5, the temperature is raised to 900° C. and maintained at 900° C. for 5 minutes to grow four layers of crystals.
[0078] Figure 6 Schematic diagram and optical microscope image (a) of eight stacking configurations of two-dimensional four-layer MoS2 prepared in Example 4, Raman spectra of four-layer MoS2 with eight different stacking configurations (b), and fluorescence spectra of four-layer MoS2 with eight different stacking configurations (c). It can be seen that the eight stacking configurations of four-layer MoS2 are fully demonstrated under the characterization of Raman and fluorescence spectra, and the intrinsic differences of the eight stacking configurations are also verified by the displacement difference of Raman characteristic peaks and the difference between the two exciton peaks of fluorescence spectra.
[0079] Figure 7 The Stokes and Anti-Stokes ultra-low frequency Raman spectra of double-layer MoS2 in AA and AB stacking structures of Example 2, including spectra under unpolarized (un), parallel polarization ( / / ) and perpendicular polarization (⊥) conditions (a, b), the inset shows the vibration schematic diagram of the shear mode (SM, purple area) and the breathing mode (BM, green area) and the position of their characteristic peaks, the intensity ratio of BM and SM in double-layer MoS2 and the intensity ratio of parallel and perpendicular polarization (c), the Stokes and Anti-Stokes Raman spectra of triple-layer MoS2 in four stacking structures of Example 3, including spectra under unpolarized (un), parallel polarization ( / / ) and perpendicular polarization (⊥) conditions (d), the intensity ratio of parallel polarization ( / / ) and perpendicular polarization (⊥) in the triple-layer system (e), and the theoretical calculation of the electronic band structure of single-layer to quadruple-layer MoS2 of Examples 1-4 (f). We used ultra-low frequency Raman spectroscopy analysis to study the double-layer (Figure ab) and triple-layer ( Figure 7(d) Characteristic peaks of the breathing mode (BM) and shear mode (SM) of the system. Ultra-low frequency Raman spectroscopy has been widely used to identify the crystalline phase or stacking order of few-layer TMDCs. In addition, the unique features of the shear mode and breathing mode were successfully identified by parallel and perpendicular polarization measurements, which helps to accurately determine the subtle changes in the stacking order of different layers. Figure 7 The intensity ratio of BM to SM (expressed as I B / I S ) can be effectively used as a parameter to distinguish the bilayer regions in two bilayer samples. B / I S ~0.4 is identified as AB superposition, while I B / I S ~0.85 is identified as AA, ( Figure 7 The pink coordinate axis in c indicates that the interlayer coupling is stronger than that of AB. However, in the three-layer system, we found that SM and BM almost merged into one peak in the ultra-low frequency Raman spectrum, indicating that their respective intensities are not as obvious as those observed in the two-layer system. Therefore, I B / I S The ratio cannot be used directly to identify the stacking structure of the three layers. In our method to quantitatively evaluate the difference between the two modes, we used polarization techniques. This method helps to clearly distinguish between SM and the samples parallel to the plane (I / / ) and vertical (I ⊥ ) of the BM. In this case, I / / is the sum of the parallel components of SM and BM. On the contrary, I ⊥ It consists only of the vertical component of the SM, which results in the BM being completely ineffective in the vertically polarized configuration. Therefore, for the three-layer system, I B / I S The ratio is converted to I / / I ⊥ Now, among the three layers, I B / I S Refers to the strength ratio between the bottom two layers of a three-layer structure. / / I ⊥ (AB stacking is about 2.5, AA stacking is about 4, Figure 7 The purple coordinate axis of c) and the I / / I ⊥ (ABA is about 3, AAB and ABB are about 6, AAA is close to 9, Figure 7 The purple coordinate axis in e) and the interlayer BM and SM intensity ratio ( Figure 7 The comparative analysis of the pink coordinate axis in e is shown in Figure c, e. From the perspective of the three layers, Figure 7 E of AAA of I / / I⊥ The intensity ratio is the highest, followed by AAB and ABB, and ABA is the lowest. This clearly shows that the intensity ratio depends on the stacking structure of double-layer and triple-layer MoS2, providing a valuable tool for determining the stacking order of few-layer MoS2. In general, in ultra-low frequency Raman spectroscopy, whether using I B / I S Or I / / I ⊥ The information of its stacking structure and strength changes can be obtained, but I / / I ⊥ The factors taken into consideration are more comprehensive, and the changing trends are relatively consistent.
[0080] Figure 8 The angle-resolved polarization Raman spectrum (a) and the angle-resolved polarization Raman spectrum (b) of the two-dimensional monolayer MoS2 prepared in Example 1 with parallel polarization configuration, the angle-resolved polarization Raman spectrum (c) and the angle-resolved polarization Raman spectrum (d) of the AA(A) stacking configuration with parallel polarization configuration and the angle-resolved polarization Raman spectrum (e) and the angle-resolved polarization Raman spectrum (f) of the AB(B) stacking configuration with parallel polarization configuration and the angle-resolved polarization Raman spectrum (f) of the vertical polarization configuration in Example 2-4.
[0081] Comparative Example 1
[0082] Same as Example 1, except that no NaCl powder is added to S4.
[0083] Comparative Example 2
[0084] Same as Example 1, except that the amount of NaCl powder added in S4 is 1.0 mg.
[0085] Comparative Example 3
[0086] Same as Example 1, except that the amount of NaCl powder added in S4 is 0.8 mg.
[0087] Comparative Example 4
[0088] Same as Example 1, except that the amount of NaCl powder added in S4 is 0.5 mg.
[0089] Comparative Example 5
[0090] Same as Example 1, except that the amount of NaCl powder added in S4 is 0.3 mg.
[0091] Fig. 9The optical microscope images of MoS2 crystals prepared by adding different amounts of NaCl in Comparative Examples 1 to 5. When no NaCl is added (i.e., Comparative Example 1), MoS2 with regular morphology cannot be grown, or even cannot be grown; when 1.0 mg NaCl is added (i.e., Comparative Example 2), it will fuse and deteriorate the growth environment at high temperature, and cause a violent reaction and no MoS2 crystals can be obtained; when 0.8 mg NaCl is added (i.e., Comparative Example 3), the auxiliary agent can quickly reduce the melting point of MoO3, but the growth environment is still deteriorated, resulting in only the nucleation points of MoS2 crystals being generated to limit their lateral growth; when 0.5 mg NaCl is added, the MoS2 crystals can only grow at the nucleation points, which can limit their lateral growth. When NaCl is added (i.e., Comparative Example 4), MoS2 crystals can be grown rapidly, but the growth rate cannot be controlled, resulting in irregular morphology; when 0.3 mg NaCl is added (i.e., Comparative Example 5), MoS2 crystals can be grown rapidly and the morphology is a regular triangle, but the distribution of the number of layers cannot be accurately controlled, and it can be seen that the thickness is uneven, which is suitable for multi-layer growth; these data show that in order to ensure that the content of NaCl auxiliary agent cannot be too little or too much, only by selecting an accurate amount (0.1 mg) can high-quality MoS2 crystals with regular morphology and controllable number of layers be grown (Note: In order to illustrate the accuracy of this phenomenon, at least three batches are used to prove the repeatability and reliability of the experiment).
[0092] Fig.10 The optical microscope images of MoS2 crystals with different numbers of layers grown under different growth temperatures (700°C, 720°C, 850°C and 900°C) in Examples 1 to 4 show that adjusting the growth temperature under appropriate NaCl auxiliary agent content can more accurately achieve precise control of the number of layers from single layer to four layers. The dual coupling effect of temperature gradient and auxiliary agent was verified again (Note: In order to illustrate the accuracy of this phenomenon, at least three batches were used to prove the repeatability and reliability of the experiment. In the experiment, a single layer can be repeatedly produced, but the size of the single-layer triangle is not fixed. Some triangles are large, and some are small. Therefore, different magnifications were selected to see the single-layer triangles more clearly).
[0093] Comparative Example 6
[0094] The difference from Example 1 is that in step S5, the temperature is raised to 930°C and maintained at 930°C for 5 minutes to allow crystal growth.
[0095] Fig.11 This is an optical microscope image of a sample grown at a growth temperature of more than 900°C in Comparative Example 6. It can be seen that the number of layers exceeds five or even more layers, proving that the temperature gradient has limitations in achieving crystal preparation with more layers, or that the temperature gradient needs to be more finely regulated. Only within 700-900°C can the regulation of the number of layers have a very significant effect, which indirectly proves the key role of the temperature gradient.
[0096] Application Example 1
[0097] The single-layer MoS2 crystal prepared in Example 1 was made into a photodetector. The specific preparation process was as follows: the device was prepared based on the single-layer MoS2 crystal synthesized in Example 1, and the electrode formed by thermally evaporating Au with a thickness of 150nm using a mask plate was transferred to the MoS2 crystal as a source electrode and a drain electrode. Four different wavelengths of light (including 365nm, 405nm, 450nm and 515nm) were used as light sources, as well as a light source with a fixed wavelength and different illumination powers to obtain a photodetector.
[0098] The single-layer MoS2 photodetector prepared in Example 1 was tested for electrical and photoelectric properties using a probe station. Fig.12 and Fig.13 . Fig.12 IV curve (a) of the photodetector based on single-layer MoS2 crystal prepared in Example 1 under irradiation with light sources of different wavelengths, photosensitivity (b), responsivity (c) and detection rate (d) under light sources of different wavelengths; By comparing the dark current and the photocurrent response with different wavelengths, the light response after adding light shows a trend of first increasing and then decreasing as the wavelength increases from 365nm to 515nm, and the maximum corresponding wavelength is at 405nm. It can be clearly seen that the single-layer MoS2 crystal prepared by this method has the highest responsivity to 405nm.
[0099] Fig.13 IV curves (a) of the photodetector based on the single-layer MoS2 crystal prepared in Example 1 at different light intensities at 405 nm, photosensitivity (b), responsivity (c) and detection rate (d) at different light intensities; Fig.13 Under 405nm light, the optical power is 4.54μW·cm -2 To 129.8μW·cm -2 The power dependence of the photodetector was studied in the range of . The results showed that the photocurrent increased significantly with the increase of light intensity. In addition, the photosensitivity of the photodetector prepared in Example 1 was 2.3×10 3 , the response rate is 3.3×10 4 A.W. -1 , the detection rate can reach 1.7×10 14 Jones. In summary, the above device indicators all show that this photodetector outperforms most photodetectors based on two-dimensional materials, especially in the phototransistor based on molybdenum disulfide, which has ultra-high photoresponse characteristics, the highest value reported in this field.
[0100] Application Example 2
[0101] The two-dimensional 1-3 layer MoS2 crystals prepared in Examples 1-3 are made into polarization-sensitive photodetectors. The structure of the photodetector is shown in FIG. Fig.14 In a, the specific preparation process is: based on the two-dimensional 1-3 layer MoS2 crystal synthesized in Examples 1-3, the electrode formed by thermally evaporating Au with a thickness of 150nm through a mask is transferred to the MoS2 crystal as the source electrode and the drain electrode, light with a wavelength of 405nm is used as the light source, and a half-wave plate is placed above the light source to change the direction of the light source, thereby obtaining a polarization-sensitive photodetector.
[0102] The polarization-sensitive photodetectors prepared in Examples 1-3 were tested electrically and photoelectrically using a probe station. The direction of the laser beam was changed by rotating the half-wave plate. The results are shown in Fig.14 . Fig.14 The structure diagram of the polarization-sensitive photodetector prepared in Example 1 (a), the IT curve of the polarization-dependent photocurrent response of 1-3 layers of MoS2 crystal prepared in Examples 1-3 (b), the polarization-dependent photocurrent polar coordinate diagram (c), and the characteristic light response time curve (d) in the fast scanning mode. Fig.14 As can be seen from part b, when the direction of the laser beam changes periodically over time, a periodically changing photocurrent will be generated. Fig.14 Extract the data from part b of the diagram and plot the polarization-dependent photocurrent in polar coordinates, as shown in Fig.14 As shown in part c. Fig.14 Part c shows that the photocurrent changes periodically with the rotation angle, with maximum values at 90° and 270° and minimum values at 0° and 180°. The anisotropy ratios of the photocurrents obtained from 1-3 layers of MoS2 crystals were calculated to be 1.36, 1.44, and 1.52, respectively. The above results show that the two MoS2 crystals prepared in Example 1 have strong in-plane photoelectric anisotropy, providing an ideal platform for multifunctional optoelectronic devices.
[0103] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for growing molybdenum disulfide crystal layers and stacking structures based on temperature gradient control, characterized in that: Using molybdenum trioxide powder and sulfur powder as precursors and sodium chloride as an auxiliary agent, chemical vapor deposition is carried out and the growth temperature is controlled at 700-900°C to obtain molybdenum disulfide crystals with controllable number of layers and stacking structure.
2. The method for growing molybdenum disulfide crystals based on temperature gradient control and stacking structure according to claim 1, characterized in that: The mass ratio of the molybdenum trioxide powder, the sulfur powder and the sodium chloride is 1:100:0.
1.
3. The method for growing molybdenum disulfide crystals based on temperature gradient control and stacking structure according to claim 1, characterized in that: The chemical vapor deposition step includes: mixing the molybdenum trioxide powder and the sodium chloride and placing them at the heat source center of a tube furnace, placing the sulfur powder upstream of the tube furnace 15 cm away from the heat source center, placing the SiO2 surface of the Si / SiO2 substrate face to face with the molybdenum trioxide powder and the sodium chloride, and placing the Si / SiO2 substrate directly above the molybdenum trioxide powder and the sodium chloride, heating to the growth temperature for crystal growth, cooling to room temperature after the growth is completed, and obtaining molybdenum disulfide crystals with controllable number of layers and stacking structure.
4. The method for growing molybdenum disulfide crystals based on temperature gradient control and stacking structure according to claim 3, characterized in that: The distance between the molybdenum trioxide powder and the sodium chloride and the Si / SiO2 substrate is 4 mm.
5. The method for growing molybdenum disulfide crystals based on temperature gradient control and stacking structure according to claim 3, characterized in that: The Si / SiO2 substrate also includes a pretreatment step before use; the pretreatment method is: cutting the wafer-level Si / SiO2 into independent substrates of 1cm×1cm size, ultrasonically cleaning them with ultrapure water, acetone, isopropanol and ethanol respectively, with an ultrasonic power of 40W, each ultrasonic cleaning for 10 minutes, and finally blowing dry with nitrogen to use as the crystal growth surface.
6. The method for growing molybdenum disulfide crystals based on temperature gradient control and stacking structure according to claim 1, characterized in that: A single-layer molybdenum disulfide crystal is obtained at a growth temperature of 700°C, a double-layer molybdenum disulfide crystal is obtained at a growth temperature of 720°C, a triple-layer molybdenum disulfide crystal is obtained at a growth temperature of 850°C, and a quadruple-layer molybdenum disulfide crystal is obtained at a growth temperature of 900°C.
7. The method for growing molybdenum disulfide crystals based on temperature gradient control and stacking structure according to claim 1, characterized in that: During the chemical vapor deposition, the crystal growth time is controlled to be 5 minutes.
8. A molybdenum disulfide crystal with controllable number of layers and stacking structure, characterized in that: Obtained according to the growth method according to any one of claims 1 to 7.
9. The molybdenum disulfide crystal with controllable number of layers and stacking structure according to claim 8, characterized in that: The average thickness of the molybdenum disulfide crystal monolayer is 0.71 nm, the average thickness of the double layer is 1.26 nm, the average thickness of the triple layer is 1.85 nm, the average thickness of the quadruple layer is 2.29 nm, and the maximum lateral dimension is 210 μm.
10. Application of the molybdenum disulfide crystal with controllable layer number and stacking structure as claimed in claim 8 or 9 in the field of optoelectronics.
Citation Information
Patent Citations
Method for preparing large-area two-dimensional molybdenum diselenide films with different layer numbers and application
CN111960388A
Preparation method of two-dimensional molybdenum sulfide crystal material with special morphology
CN112663139A
Preparation method of double-layer molybdenum sulfide crystal material with different coverage rates
CN113957538A
Preparation method of tin sulfide / molybdenum disulfide mixed dimension van der Waals heterojunction
CN114959635A
Ectopic nucleation double-layer MoS2 nanosheet and preparation method thereof
CN115156524A
Cited By
A high-density three-dimensional spiral pyramidal molybdenum disulfide catalytic membrane, a preparation method thereof and a hydrogen evolution application thereof
CN122897438A